On the Significance of New Biochemical Markers for the Diagnosis of Premature Labour - Rafał Rzepka; Barbara Dołęgowska; Aleksandra Rajewska; Sebastian Kwiatkowski (Mediators of Inflammation)
Preterm labour is defined as a birth taking place between 22nd and 37th weeks of gestation. Despite numerous studies on the aetiology and pathogenesis of preterm labour, its very cause still remains unclear. The importance of the cytokines and acute inflammation in preterm labour aetiology is nowadays well-proven. However, chronic inflammation as an element of the pathogenesis of premature labour is still unclear. This paper presents a literature review on the damage-associated molecular patterns (DAMPs), receptors for advanced glycation end products (RAGE), negative soluble isoforms of RAGE, chemokine-stromal cell-derived factor-1 (SDF-1) and one of the adipokines, resistin, in the pathogenesis of preterm labour. We conclude that the chronic inflammatory response can play a much more important role in the pathogenesis of preterm delivery than the acute one.